2017
DOI: 10.1016/j.watres.2017.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Use of gas chromatography–mass spectrometry–olfactometry and a conventional flask test to identify off-flavor compounds generated from phenylalanine during chlorination of drinking water

Abstract: Off-flavor in drinking water can be caused by transformation products (TPs) generated from organic compounds, such as amino acids, present during chlorination. However, the contributions of many of these TPs to overall off-flavor have not been quantified, mainly because the lack of appropriate chemical standards prevents sensory evaluation by means of a conventional flask test. In the present study, we used gas chromatography-mass spectrometry-olfactometry (GC-MS-O) to identify compounds responsible for the of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Because a substantial portion of bromamines decay and release ammonia within a few hours, the NHCl₂, NCl₃, and free chlorine that persisted initially were likely able to tie‐up a portion of the free ammonia released (Figure S4). While ratios >5:1 form NHCl₂ and NCl₃ that can cause taste and odor problems, the maximum NHCl₂ and NCl₃ simulated concentrations for all conditions were 0.16 mg‐Cl₂/L and 0.012‐Cl₂/L, respectively, which would not be expected to cause aesthetic issues (Figure S4) (Matsushita et al, 2017; Suffet et al, 2004). However, at a lower pH, these odorant levels would be higher and could be problematic.…”
Section: Resultsmentioning
confidence: 99%
“…Because a substantial portion of bromamines decay and release ammonia within a few hours, the NHCl₂, NCl₃, and free chlorine that persisted initially were likely able to tie‐up a portion of the free ammonia released (Figure S4). While ratios >5:1 form NHCl₂ and NCl₃ that can cause taste and odor problems, the maximum NHCl₂ and NCl₃ simulated concentrations for all conditions were 0.16 mg‐Cl₂/L and 0.012‐Cl₂/L, respectively, which would not be expected to cause aesthetic issues (Figure S4) (Matsushita et al, 2017; Suffet et al, 2004). However, at a lower pH, these odorant levels would be higher and could be problematic.…”
Section: Resultsmentioning
confidence: 99%
“…That is to say, GC-O enables us to conduct sensory and instrumental analysis simultaneously. For instance, Matsushita et al utilized GC-O-MS and identified N-chlorophenylacetaldimine and 2-chloro-2-phenylacetaldehyde as the odorants responsible for the off-flavor that had been generated by chlorination [92]. Employing MVA or GC-O, or using them in combination is a competent approach to determine a candidate chromatographic peak of fishy odorants.…”
Section: Approach Required To Solve the Problemmentioning
confidence: 99%
“…For example, previous studies of laboratory chlorination of mg/L of Phe have identified N-chlorophenylacetaldimine with an odor threshold of 3−4 μg/L, and it has been linked with odor events in drinking water. 36,42 However, AAs make up a small portion of the total organic matter present in water, and thus a change in AA concentration may not result in changes to common water quality parameters which are used by operators to guide water treatment performance. No study has systematically investigated the occurrence of AAs in source water and odor profiles in home taps, because odor events are unpredictable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that laboratory chlorination and chloramination of AAs can produce aldehydes, N -chloroaldimines, and nitriles, which are odor-causing compounds that are often characterized as chlorinous odors. ,,, Compounds formed from AAs, particularly phenylalanine (Phe), leucine (Leu), isoleucine (Ile), and valine (Val), have been suggested as sources of odor concerns because their odor thresholds are as low as 150 ng/L. ,,, Several studies reported that AAs in environmental water occurred at ranges of 500 to 30,000 ng/L. ,,, Environmental levels of AAs in source water could potentially produce odorous DBPs at levels above the odor threshold during chlorination. For example, previous studies of laboratory chlorination of mg/L of Phe have identified N -chlorophenylacetaldimine with an odor threshold of 3–4 μg/L, and it has been linked with odor events in drinking water. , However, AAs make up a small portion of the total organic matter present in water, and thus a change in AA concentration may not result in changes to common water quality parameters which are used by operators to guide water treatment performance. No study has systematically investigated the occurrence of AAs in source water and odor profiles in home taps, because odor events are unpredictable.…”
Section: Introductionmentioning
confidence: 99%